DETERMINATION OF THE PERIOD OF MARKOV CHAIN’S TRANSITION MATRIX FOR MILITARY MANPOWER PLANNING IN INDONESIAN NAVY - Wahyuli, Agus (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2019)
Â Abstract Â Â Human resources are very important organizational assets thus it is only natural that every organization gives more attention to human resource management, including the Indonesian Navy (TNI AL). The approach to human resource planning in military organizations focuses on two aspects, including long term planning with strategic objectives and short term planning with operational objectives. This long term planning is oriented towards the continuation of the procurement, availability, and balance of the number of personnel (human resources) in each rank in the future. An analysis to find out and plan the condition of Navy personnel in the future is needed, which is called the analysis of the Markov chain. There are at least three stages of the Markov chain process, including determining the state, the transition matrix, and the initial vector value. The transition matrix describes changes from one state to another state in the next period of time. The transition matrix formed is the basis of the subsequent analysis, including the calculation of the number of personnel per rank in the future. Determining the length of the matrix period is done by comparing several transition matrices with various moving average orders. The result obtained suggests that the best transition matrix is the one with moving average orders six, including the transition matrix with the smallest value of Mean Square Error (MSE). Â Keywords: Markov Chain, Military Manpower Planning, Transition Matrix, Indonesian Navy Â